CoCrFeNiTi High Entropy Alloy Prepared via Mechanical Alloying and Spark Plasma Sintering - Kratochvíl, Petr; Průša, Filip (Manufacturing Technology Journal, 2022)
Mechanical alloying and subsequent compaction with spark plasma sintering was chosen for the fabrication of investigated CoCrFeNiTi alloy method. The alloy was characterized in terms of chemical and phase composition with X-ray fluorescence spectroscopy and X-ray diffraction spectrometry, respectively. The microstructure was examined using light microscopy and scanning electron microscopy equipped with an energy dispersion spectrometer. The alloy showed an ultra-fine grained uniform microstructure composed mainly of an FCC solid solution with a volume fraction of HCP Laves phases. Regarding mechanical properties, the prepared specimen reached an ultimate compressive strength of 1340 MPa with the hardness of 757 HV 30. The wear rate of the sample reached 1.19 . 10-4 mm3.N-1.m-1 showing traces of adhesive-abrasion wear mechanism.
Keywords: High entropy alloys; Mechanical alloying; Spark plasma sintering; Mechanical properties